The Initiatives to Strengthen Teachers' Online Learning Skills During the Covid-19 Pandemic - Tengku Muhammad Sahudra; Raja Novi Ariska; Nursamsu Nursamsu (STAI Hubbulwathan Duri, 2021)
This study aimed to ascertain measures to enhance teachers' ability to teach online during the covid 19 pandemic. Action research is the research approach used in this type of research. The research was qualitative, describing the efforts to improve teachers' abilities to incorporate online learning into the teaching and learning process. This study was conducted at the MGMP for geography teachers at the senior high school and vocational high school level in Aceh Tamiang Regency. This study shows that teachers' competency in online learning is increasing, with the first cycle having a value of 0.45 per cent and the second cycle having a value of 0.80 per cent; hence, the two cycles predict growth in instructors using online learning in the future. Teachers can utilize a variety of technology-based online learning platforms, including Google Classroom, Edmodo, Quizizz, and Schoology.